FAKTOR–FAKTOR YANG MEMPENGARUHI PRODUKSI KELAPA SAWIT RAKYAT DI KECAMATAN BANGUN PURBA KABUPATEN DELI SERDANG - Anis Khaizuran Muntazhar; Hanisah Hanisah; Siti Balqies Indra (Jurnal Cakrawala Ilmiah, 2026)
This research was conducted to determine the influence of land area, amount of roundup use, amount of NPK fertilizer use and labor on smallholder oil palm production in Bangun Purba District, Deli Serdang Regency. The technique for determining the number of samples was carried out using the Quota Sampling Technique with a sample size of 39 smallholder oil palm farmers in Bangun Purba District, Deli Serdang Regency. The data used in this research are primary data and secondary data. The data analysis technique used is Multiple Linear Regression. Data processing was carried out using the SPSS Version 22 Program. The results of this research show that Land Area, Number of Uses of NPK Fertilizer and Labor have a significant effect on People's Palm Oil Production in Bangun Purba District, Deli Serdang Regency and the Variable Number of Uses of Roundup does not have a significant effect on Coconut Production People's Palm Oil in Bangun Purba District, Deli Serdang Regency